Metastatic HER-2-positive salivary gland carcinoma treated with trastuzumab and a taxane: a series of six patients. Issue 6 (1st November 2016) - De Block, Katrien; Vander Poorten, Vincent; Dormaar, Titiaan; Nuyts, Sandra; Hauben, Esther; Floris, Giuseppe; Deroose, Christophe M.; Schöffski, Patrick; Clement, Paul M.
Abstract : Metastatic salivary gland carcinoma is a rare malignancy. A subset of these tumors overexpresses the human epidermal growth factor receptor 2 (HER-2), which is considered a poor prognostic marker. Targeted therapy with the monoclonal antibody trastuzumab can be a treatment option in these patients. We describe six cases of metastatic salivary gland carcinoma treated with trastuzumab in combination with a taxane. Three of these patients had salivary duct cancer, two had mucoepidermoid carcinoma and one patient was treated for acinic cell carcinoma. The therapy was well tolerated. We observed five partial responses and a median progression free survival of 10.8 months, which compares favorably with the reported outcome of combination chemotherapy. One patient achieved a complete and durable remission. When HER-2 and androgen receptor were co-expressed, trastuzumab-based treatment appeared to be more active than androgen deprivation in our experience.